Music Projects in Primary School - Gregorič, Anja (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter presents music projects in primary school that includes activities such as singing, playing musical instruments, moving to music and listening. These projects encourage creativity, the expression of emotions and critical thinking in pupils. The importance of adapting the learning process to the needs and abilities of the pupils and the role of teachers in shaping the quality of the musical experience is emphasised. Research highlights the benefits of group work, such as social cohesion and cooperation, and individual work, which allows a focus on individual progress. The interdisciplinary nature of the projects, combining music with other areas such as dance, language and science, contributes to children's holistic development and increases their interest in music. Music projects are thus an important tool for developing pupils' skills and creativity.